Mineralogy of fine-grained matrix, fine-grained rim, chondrule rim, and altered mesostasis of a chondrule in Asuka 12169, one of the least altered CM chondrites - Noguchi, Takaaki; Yasutake, Masahiro; Tsuchiyama, Akira; Miyake, Akira; Kimura, Makoto; Yamaguchi, Akira; Imae, Naoya; Uesugi, Kentaro; Takeuchi, Akihisa (Polar Science, 2021)
Mineralogy of fine-grained matrix (FGM), fine-grained rim (FGR), chondrule rim, and altered mesostasis of a chondrule from the Asuka (A) 12169 CM3.0 chondrite was investigated by field emission scanning electron microscopy (FE-SEM), synchrotron radiation-based X-ray nano-tomography (SR-XCT), and transmission electron microscopy (TEM). SR-XCT and TEM observations revealed that both FGM and FGR contain abundant amorphous silicate embedding nano-inclusions (most are Fe–Ni sulfide). Although the amorphous silicate is more or less hydrated based on the analysis of the X-ray linear attenuation coefficients in SR-XCT, there are no areas filled by abundant phyllosilicate even in three dimensions. However, FGM and FGR contain ~2-10 μm-sized aggregates composed of tochilinite, nano-inclusions of possible magnetite, and poorly crystalline serpentine without sharp boundaries with the surroundings. It is unlikely that the heterogeneity resulted from brecciation and mixing of materials that experienced different degrees of aqueous alteration, but more likely from a very early stage of aqueous alteration that proceeded heterogeneously depending on locally different chemistry. Chondrule mesostasis near the surface of a chondrule was altered to saponite with tochilinite-rich aggregates. These observations indicate that the degree aqueous alteration of A 12169 is very low and that it is comparable with that of Acfer 094, ALH 77307, and the least altered areas of Paris. journal article